Essentially Small Quasi-Dedekind Module Relative to a Module - Hussein, Mukdad Qaess; Salih, Marrwa Abdallah; Hussen, Nagham Ali (Al-Nahrain Journal of Science, 2018)
Let R be a ring with identity and let M be a unitary left module over R. In this paper, we study direct summand (direct sum) of essentially small quasi-Dedekind module (essentially small quasi-Dedekind modules). Also, give the definition of essentially small quasi-Dedekind relative to a module with some examples. We give some of their basic properties and some examples that illustrate these properties.